Introduction to the special issue on advancing assessment of, and interventions for, eating disorders via innovative uses of technology - Bauer, Stephanie; Goldschmidt, Andrea B. (The international journal of eating disorders, 2019)
The aim of this editorial is to introduce a Special Issue of the International Journal of Eating Disorders on “Advancing Assessment of, and Interventions for, Eating Disorders via Innovative Uses of Technology.” The 10 contributions to the Special Issue focus on the following main questions: (a) How can we optimize technology-enhanced interventions for eating disorders? (b) To what extent can technology help professionals to reach underserved populations? (c) How can innovative technology-enhanced tools improve assessment and treatment of eating disorders? The findings cumulatively suggest that technology can play a critical role in the detection and treatment of eating disorders, and may be used to enhance understanding of the etiology, maintenance, and course of these conditions. The contributions to this Special Issue have important implications for the conceptualization, design, and evaluation of technology-enhanced interventions as well as for the optimization of current assessment methods. Hopefully, they will stimulate future research in this quickly evolving field.